IMPLEMENTASI PROYEK ECOPRINT TEKNIK POUNDING DALAM PEMBELAJARAN SENI RUPA PADA KREATIVITAS SENI SISWA KELAS IV SD NEGERI 04 JATISOBO - Eni Wulandari; I Made Ratih Rosanawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of an ecoprint project using the pounding technique and its contribution to students' artistic creativity in fourth-grade visual arts learning at SD Negeri 04 Jatisobo. This research employed a descriptive qualitative approach. The research subjects consisted of one fourth-grade teacher and fifteen students selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, supported by NVivo software. The results showed that the implementation of the ecoprint pounding technique project stimulated students' artistic creativity through four aspects of creativity: fluency, flexibility, originality, and elaboration. Students actively explored various natural materials, experimented with leaf arrangements, and developed unique artistic compositions. The ecoprint project also provided meaningful learning experiences that increased students’ enthusiasm, creativity, and environmental awareness. Therefore, the ecoprint pounding technique can be considered an innovative and contextual learning strategy to develop artistic creativity in elementary school students.